The effects of tax structure on economic growth: evidence from Pakistan economies - khan, Mahfooz; Ul amin, Saif; Khan, Sammandar (International Journal of Accounting and Economics Studies, 2016)
The study has been conducted to find out the effects of fiscal policy on economic growth in Pakistan. Taxes are selected as a proxy for fiscal policy and GDP as an economic growth. In this study the time series analysis was used. The study used difference tests and models. These tests were unit root test which at different levels was used for stationary and non-stationary another model was co-integration the co-integration further used two tests one was trace test and second one was maximum Eigen value these tests used for long run relationships between taxes and GDP. In this study Granger causality test lag 2 and lag 4 also for checking the effects of taxes on Pakistan GDP. The objectives of the study are to find out the relationship between taxes and GDP and also to testify the random walk between taxes and GDP. The data were taken from 1981 to 2012. Taxes dealt as an independent and GDP as a dependent variable of the study. Data were collected from Federal Bureau of Statistics and from Pakistan economic survey. Time series analysis is used to testify the hypotheses. The results of Unit Root test shows that GDP and taxes has a unit root and it is non- stationary. GDP has no unit root and stationary in nature at 1st difference level. The results of co-integration shows that both taxes and GDP no co-integration at 5 % level of significance. The study concludes that there is no Co-integration between taxes and GDP. The study recommended that fiscal policy should make according to the situation of the country and the tax rate should be change with a smooth rate.
Keywords: Taxes; Fiscal Policy; GDP; Economic Growth; Pakistan.